Scale for maternity role perceptions-short form validity and reliability study - Zümrüt Bilgin; Şule Ecevit Alpar (Pediomaternal Nursing Journal, 2026)
Background: The maternal role is the process of learning and achieving maternal behavior. It is important to identify and support mothers' role perceptions.The first version of the Maternal Role Perception Scale consists of 28 items. Objective: This study was conducted to develop a short form of the Maternal Role Perception Scale. Method: This methodological study was conducted in a hospital between September 01, 2021 and November 26, 2021. In this study, the sample consisted of 279 mothers between the ages of 18 and 45 who consented to participate in the study. The validity and reliability of the scale were analyzed by exploratory and confirmatory factor analysis and Cronbach's alpha coefficients. Data were analyzed with IBM SPSS and AMOS demo programs. Results: As a result of the exploratory factor analysis, the Maternal Role Perception Scale-Short Form consisted of 15 items and two factors explaining 53.875% of the total variance. After the application, 13 items with item loadings below 0.45 were removed from the scale. The item-total correlation of the fifteen-item Maternal Role Perceptions Scale-Short Form was between 0.348 and 0.724, and the Cronbach's Alpha reliability coefficient was found to be 0.896. Confirmatory factor analysis was conducted on the short form of the scale consisting of two factors. As a result of the analysis, the Adjusted Goodness of Fit Index and the Goodness of Fit Index were found to be adequate. Conclusion: The Maternal Role Perception Scale-Short Form, which consists of fifteen items and two factors, is a valid and reliable measurement tool that can be used to measure mothers' maternal role perceptions. Keywords: Maternal role; maternity role perception; reliability; validity